G32(P) Late preterm infants at greater risk of paediatric intensive care admission and longer invasive ventilation due to respiratory syncitial virus bronchiolitis. (12th March 2018) - Followell, S; Christopherson, M; Davis, P
Abstract : Aims: Only a small proportion of late-preterm (LPT) infants (34–36+6 weeks gestational age) require admission to NICU for respiratory support at birth. We aimed to evaluate the subsequent impact of Respiratory Syncitial Virus (RSV) on LPT infants compared to FT infants. Methods: A retrospective cohort study of infants admitted to a regional tertiary PICU with a primary diagnosis of RSV-positive bronchiolitis over a five-year period was undertaken. LPT infants were compared to FT infants (37 weeks and greater gestational age). The relative risk of PICU admission for RSV-positive bronchiolitis for LPT and FT infants in our regional population was calculated using Office of National Statistics data. Ventilation rates between the 2 groups admitted to PICU were compared using Chi-squared. Non-parametric statistical analysis was undertaken to identify any significant differences in other resource utilisation between the LPT and FT infants. Results: 40 LPT and 102 FT infants were admitted to PICU with a diagnosis of RSV-positive bronchiolitis from 2012 to 2017. Of infants born between 34 and 42 weeks in this period, 4.4% were LPT. However, LPT infants constituted 28.2% of the study population admitted to PICU with RSV-positive bronchiolitis (RR=8.44, 95% CI 5.85–12.15, p<0.0001). Invasive ventilation rates were similar between LPT and FT infants (75% LPT vs. 68.6% FT, χ2=0.08, DF1, p=0.78). The median length of invasive ventilation was 6 days (IQR 5–11) among LPT infants and 5 days (IQR 4–7) for FT infants (W=1322; p=0.039). The median length of PICU stay was 7 days (IQR 5–12) for LPT infants and 6 days (IQR 4–8) among FT infants (W=2574; p=0.015). There were no PICU deaths among the 142 RSV-positive bronchiolitis admissions. Conclusion: Despite few LPT infants requiring respiratory input from a neonatologist at birth, following discharge home, they are at significantly increased risk of admission to PICU with RSV-positive bronchiolitis, compared to FT infants, with longer periods of invasive ventilation and lengthier admissions. This may reflect the importance of reaching full term for lung development and the control of breathing, especially when exposed to common respiratory viruses during infancy.